2018
DOI: 10.1038/s41598-018-20649-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microbiome and associated immune markers: New insights into the pathogenesis of vaginal dysbiosis

Abstract: The microbiota fulfils a key role in the training and function of the immune system, which contributes to the symbiosis between the host and complex microbial communities. In this study, we characterized the interplay between vaginal bacteria and local immune mediators during dysbiosis in selected women of reproductive age who were grouped according to Nugent’s criteria. The abundance of Gardnerella vaginalis and Bifidobacterium breve was increased in the intermediate dysbiotic status, while the presence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…Taken together, we cannot exclude for a possible contribution of these core gut microbiota in promoting advanced PCa presentation within Africa. Associations to consider include, Bacteroides abundance within vaginal communities of women with bacterial vaginosis (BV), a common condition impacting southern African women, and Bacteroides abundance within the gut mucosa of patients with colorectal cancer …”
Section: Discussionmentioning
confidence: 99%
“…Taken together, we cannot exclude for a possible contribution of these core gut microbiota in promoting advanced PCa presentation within Africa. Associations to consider include, Bacteroides abundance within vaginal communities of women with bacterial vaginosis (BV), a common condition impacting southern African women, and Bacteroides abundance within the gut mucosa of patients with colorectal cancer …”
Section: Discussionmentioning
confidence: 99%
“…Immediately before the oocyte retrieval, the vagina was irrigated with 50 mL of sterile water, and 3 mL of cervico‐vaginal lavage fluid was collected for our investigations. Cytokine analysis was performed using magnetic bead‐based multiplex immunoassays (Bio‐Plex®; BIO‐RAD Laboratories, Milano, Italy) using the Bio‐Plex 200 reader (Luminex, Austin, TX, USA), as previously described . In brief, 50 µL of cervico‐vaginal washing and standards was added in duplicate to a 96‐multiwell plate containing analyte beads.…”
Section: Methodsmentioning
confidence: 99%
“…These results suggest that there are significant differences in vaginal microbiota related to ancestry (53); such differences might explain the observed prevalence of bacterial vaginosis and preterm birth. Vaginal dysbiosis is associated with increased levels of proinflammatory cytokines (58). Recently, Fettweis et al (53) observed that levels of the vaginal inflammatory cytokine CXCL10 were related to the L. crispatus/L.…”
Section: The Vaginal Microbiotamentioning
confidence: 99%